Associação entre o polimorfismo genético da apolipoproteína-B e fatores de risco cardíaco em pacientes da região dos Campos Gerais-PR - Hoffmann, Lucia (2012)
Apolipoprotein B (apoB) is the principal protein from low density lipoprotein (LDL) involved in cholesterol metabolism and transport. Single nucleotide polymorphisms (SNPs) in the human apoB gene have been associated with cardiovascular disease risk, such as Coronary Artery Disease (CAD), dyslipidemia and atherosclerosis. These multifactorial diseases are generated by interaction between environmental and genetic factors. Previous works investigated the genetic causative components of these diseases and focused mainly on polymorphisms that occur in genes encoding structural proteins and enzymes related to lipid profile. The present study aimed to investigate the MspI polymorphism in the apoB gene association with cardiovascular risk factors in a case-control patients group from the Campos Gerais region (Paraná, Brazil) population, moreover to determine this polymorphism allele and genotype frequencies, and also to associate the obtained genetic data with cardiac risk related variables by using correlation analysis. We evaluated 66 patients, from which 55 patients formed the cardiovascular risk group, and 11 others composed the group without risk – control. The patients mean age was 60 ± 10.0 years in the group with risk and 53 ± 14.0 years in the control group. The MspI polymorphism (exon 26) on apoB gene was characterized by PCR-RFLP and, after restriction, DNA fragments were identified by electrophoresis using agarose gel. The normal allele was named M1 and the mutated allele was called M2. The obtained values for MspI polymorphism genotypic frequencies were 0.82, 0.09, 0.09 for the control group, and 0.76, 0.24, 0.00 for the CAD risk group, respectively for genotypes M1M1, M1M2, M2M2. It was showed that the M1M1 homozygous was dominant in the genotype distribution for both groups. There was no significant difference between the allele and genotype frequencies for MspI polymorphism in the apoB gene (2 = 5.90, P > 0.05; Contingency Test) when comparing the two groups. Therefore, the distribution of the studied polymorphism in the Campos Gerais region population presented to be in Hardy-Weinberg equilibrium both for the control group and for the CAD risk patients group, keeping stable the polymorphism, what was already previously reported for Chinese and Korean populations. The Pearson correlation analysis performed between the risk variables (age, diabetes mellitus, high LDL, high triglycerides, low HDL, hypothyroidism, weight, body mass index) showed correlation between the most of the variables for M1M1 and M1M2 genotypes. But for the total population (n = 66), the association of the apoB gene polymorphism was not correlated with cardiac risk variables. In the end, this research presented data for understanding the association of apoB gene polymorphism with lipid metabolism disorder in the development of risk factors for cardiovascular disease in the population of Campos Gerais (PR).